A A Study on the Character Building and Messages of “Lady Windermere’s Fan” Drama by Oscar Wilde - Rahayu, Puji; Mustofa, Mutmainnah; Dyah Arini, Mercy Aprilia (Universitas Pendidikan Muhammadiyah Sorong, 2023)
This paper figures out the characters and the messages or moral values of a play namely Lady Widermere’s Fan. The drama was designed based on Heathcote’s (1984) understanding of drama in education in order to cultivate creative pedagogy and ‘character’ building. The data was gained by reading the drama script based on existing documents. The result showed that every character has various characters and each of them is related to others. The main character has fundamentally strengthened the plot and has important effects to other characters. The moral values that can be seen from this play are that all humankind is far from the word “perfect” even if they are consider themselves as good, kind, and wise people. They still tend to have shortage.